Metabolic, synaptic and behavioral impact of 5‐week chronic deep brain stimulation in hemiparkinsonian rats. Issue 5 (21st December 2015) - Chassain, Carine; Melon, Christophe; Salin, Pascal; Vitale, Flora; Couraud, Sébastien; Durif, Franck; Kerkerian‐Le Goff, Lydia; Gubellini, Paolo
Abstract: The long‐term effects and action mechanisms of subthalamic nucleus (STN) high‐frequency stimulation (HFS) for Parkinson's disease still remain poorly characterized, mainly due to the lack of experimental models relevant to clinical application. To address this issue, we performed a multilevel study in freely moving hemiparkinsonian rats undergoing 5‐week chronic STN HFS, using a portable constant‐current microstimulator. In vivo metabolic neuroimaging by 1 H‐magnetic resonance spectroscopy (11.7 T) showed that STN HFS normalized the tissue levels of the neurotransmission‐related metabolites glutamate, glutamine and GABA in both the striatum and substantia nigra reticulata (SNr), which were significantly increased in hemiparkinsonian rats, but further decreased nigral GABA levels below control values; taurine levels, which were not affected in hemiparkinsonian rats, were significantly reduced. Slice electrophysiological recordings revealed that STN HFS was, uniquely among antiparkinsonian treatments, able to restore both forms of corticostriatal synaptic plasticity, i.e. long‐term depression and potentiation, which were impaired in hemiparkinsonian rats. Behavior analysis (staircase test) showed a progressive recovery of motor skill during the stimulation period. Altogether, these data show that chronic STN HFS efficiently counteracts metabolic and synaptic defects due to dopaminergic lesion in both the striatum and SNr. Comparison of chronic STN HFS with acute and subchronic treatment further suggests that the long‐term benefits of this treatment rely both on the maintenance of acute effects and on delayed actions on the basal ganglia network. We studied the effects of chronic (5 weeks) continuous subthalamic nucleus (STN) high‐frequency stimulation (HFS) in hemiparkinsonian rats. The levels of glutamate and GABA in the striatum ( ) and substantia nigra reticulata (SNr) ( ), measured by in vivo proton magnetic resonance spectroscopy ( 1 H‐MRS), were increased by 6‐hydroxydopamine (6‐OHDA) lesion, which also disrupted corticostriatal synaptic plasticity ( ) and impaired forepaw skill ( ) in the staircase test. Five‐week STN HFS normalized glutamate and GABA levels and restored both synaptic plasticity and motor function. A partial behavioral recovery was observed at 2‐week STN HFS. Abstract : We studied the effects of chronic (5 weeks) continuous subthalamic nucleus (STN) high‐frequency stimulation (HFS) in hemiparkinsonian rats. The levels of glutamate and GABA in the striatum ( ) and substantia nigra reticulata (SNr) ( ), measured by in vivo proton magnetic resonance spectroscopy ( 1 H‐MRS), were increased by 6‐hydroxydopamine (6‐OHDA) lesion, which also disrupted corticostriatal synaptic plasticity ( ) and impaired forepaw skill ( ) in the staircase test. Five‐week STN HFS normalized glutamate and GABA levels and restored both synaptic plasticity and motor function. A partial behavioral recovery was observed at 2‐week STN HFS.